Pilgrimage ‘in between’: Religious pilgrims in main Chilean shrines (SAGE Publications, 2025)
Drawing on interviews and observation conducted at three shrines across Chile, this article examines the motivations of pilgrims in the context of the persistent vitality of religious pilgrimage in the country. While the literature on religious change in Latin America has focused on the rise of Evangelical pluralism or the increasing religious disaffiliation, this article explores the reasons behind the continuity of popular Catholicism in a changing context. Our findings reveal that, while Chilean pilgrims demonstrate motivations beyond institutionalized religion, their ties to familial community and focus on reaching a destination moderate the journey’s centrality, diverging from post-secular pilgrimage. Both the manda (religious vow) and custom integrate pilgrimage within a framework of religious obligation tied closely to familial community, thus challenging its liminoid character based on the description of pilgrimage as a journey, as well as its perceived features of voluntariness and individual autonomy.